Caesarean scar ectopic pregnancy and laparoscopy: a rendezvous - Dutta, Annesha; Koley, Murari Mohan; Kumaradasan, Sunanda; Alam, Mahfooz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Caesarean scar pregnancy (CSP) is defined as an implantation of pregnancy in a fibrous tissue scar of a previous caesarean section, one of the rarest forms of ectopic pregnancy which can be life threatening. The incidence of CSP is steadily rising in view of increasing caesarean section rates. A very high index of clinical suspicion is required for the diagnosis and further management. As with other ectopic pregnancies, caesarean scar ectopic pregnancy pose a greater risk for maternal haemorrhage and ultimately maternal mortality. Through this case report, we demonstrated the laparoscopic management of a CSP.